Phase, nanostructure, and oxidation of precursor derived SiCN–TiO2 ceramic nanocomposites. Issue 19 (1st October 2021) - Anand, Rahul; Nayak, Bibhuti B.; Behera, Shantanu K.
Abstract: Silicon and carbon containing non-oxide ceramics, such as SiC, SiCN, SiBCN, derived from polymeric precursors show outstanding resistance towards creep and oxidation at high temperatures and harsh atmospheric conditions. These polymer derived ceramics are potential materials for application as protective coatings on carbon and SiC based composites. In the current investigation, a commercially available polyvinylsilazane polymer was doped with molecular source of Ti, crosslinked and pyrolyzed in nitrogen atmosphere, and the evolution of phase and nanostructure was studied. The pyrolyzed SiTiCNO ceramic hybrids appeared predominantly amorphous up to 1000 °C. Exceptionally homogeneous distribution of anatase TiO2 nanocrystals in the size range of 2–12.5 nm was observed throughout the SiCN matrix on high temperature annealing. Such SiCN–TiO2 nanocomposites exhibit enhanced oxidation resistance till 1400 °C. The paper demonstrates easy fabrication of the ceramic nanocomposite, which promise application in high temperature barrier coatings and structural components due to its excellent crystallization and oxidation resistance.